TWO HOUSEHOLD ISSUES IN ONE AGENDA SETTING Fighting for the Protection of Domestic Workers through Settlement of Domestic Issues in Yogyakarta Palace - Ratnawati, Ratnawati Ratnawati; Santosa, Purwo (Universitas Muhammadiyah Jember, 2020)
This study focuses on the meeting of two issues in one agenda setting. On the one hand, there is an issue of protection of domestic workers, and on the other hand, there is an issue of power succession in the Yogyakarta Palace. It is about two different issues; it is not only to settle them in one process, but also to save one of the policy agendas.Â This study uses a case study. Data was collected using interviews, focus group discussions (FGD) and secondary sources. In-depth interviews and FGDs were conducted with internal parties, kingdom relatives, community leaders and activists for women's movements outside the palace. The findings of this study show that the agenda point, which brings the two issues, is gender issue, especially the role of women in the public domain. The meeting of these two issues, which leads to the opening of the policy window, involves various dynamics, including advocacy coalition, succeeded in moving policy-making rails from higher level of government, and focused more on issues at the practical-operational level. The special features of Yogyakarta actually act as a platform for actualizing local wisdom, showing the strength of cultural factors. This cultural aspect accelerates the encounter of problem streams, policy streams, and political streams, which open a window of opportunity (policy windows) for the success of a policy agenda in the agenda setting process.